Anti-Inflammatory Activity of Triterpenes Isolated from Protium paniculatum Oil-Resins. (27th December 2015) - de Almeida, Patrícia D. O.; Boleti, Ana Paula de A.; Rüdiger, André Luis; Lourenço, Geane A.; da Veiga Junior, Valdir Florêncio; Lima, Emerson S.
Abstract : Protium is the main genus of the Burseraceae family and one of the most common genera in South America, with an important species called "breu." Gum and oil-resins of this species are used as tonic and stimulant and for the treatment of ulcers and inflammation. The present study aims to isolate and investigate the anti-inflammatory activity of triterpene compounds isolated from oil-resin of Protium paniculatum . The pentacyclic triterpenes α, β -amyrin, acetylated α, β -amyrin, α, β -amyrone, and brein/maniladiol did not alter the viability of murine J774 macrophages (IC50 > 20 µ g/mL), with the exception of mixture of brein/maniladiol which showed moderate cytotoxic activity. Also it was observed that compounds at 10 µ g/mL inhibited more than 80% of production of NO, although only α, β -amyrin was able to inhibit the production of TNF- α (52.03 ± 2.4 % ). The compounds inhibited the production of IL-6 and induced the production of IL-10 in murine J774 macrophages stimulated by LPS. α, β -Amyrone inhibited the expression of COX-2 and also inhibited the formation of paw or ear edema in rats and mice, having a quick and immediate effect. This study may provide the basis for future investigations on the therapeutic role of α, β -amyrone in treating inflammation.